Edukasi Menabung Sejak Dini Guna untuk Memanajemen Keuangan Dimasa Depan Bagi Anak Anak di Mesjid Taqwa Mandala - Filyana Sabhina; Riyan Pradesyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education about saving from an early age is an important step in forming good financial management skills in children. Educational activities carried out at the Taqwa Mandala Mosque through Real Work Lectures (KKN), aim to increase children's understanding of the importance of saving and simple financial records. The research method used is a qualitative approach with counseling techniques, where children are introduced to the concept of saving using the media